An historical guide to French interiors, furniture, decoration... - Strange | Thomas Arthur (Wikimedia Commons, 1900)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Droits : Licence No known copyright restrictions via Wikimedia Commons
Keywords: histoire; iconographie; gravure; photographie; wikimedia commons; Iconographie